"Bitten by the Polar bug" : En studie om transformativa upplevelser under Students on Ice universitetsexpeditioner till Antarktis - Holmberg, Linnea; Rosenberg, Martina (2012)
There is limited research on transformative experiences and ambassadorship based on polar expeditions. This study is aimed to investigate whether college students who participated in the Students on Ice expeditions to Antarctica in 2009 and 2011 shows signs of being transformed by the experience and developed an ambassadorship to the Polar Region.By analyzing student’s experiences and feelings based on questionnaires from 2009 and 2011 together with workshop material from the 2011 expedition, we can see tendencies of the respondents that transformation and development of ambassadorship has occurred. We can not conclude that transformation has occurred just because of the polar expeditions, since a number of students say that they before already have been engaged in environmental issues and climate issues concerning Antarctica. Our own reflection from the 2011 expedition has contributed to a deeper understanding during the analysis.We also conducted a literature review to examine how to create conditions for a transformation to occur in Polar tourism from the perspective of experience production. The ambassadorship can be developed based on knowledge and understanding of the area and the environment in a global perspective. When the ambassador returns home a process begins which aim to create awareness and disseminate the knowledge to other people. The study also showed that there are models and theories that can be combined and used as tools to create conditions for transformative experiences. Validerat; 20120613 (anonymous)